Effect of the milk-whey relation over physicochemical and rheological properties on a fermented milky drink (2017)
(Eng) The effect of the milk-whey relation over the physicochemical properties (pH, total acidity, soluble solids and syneresis) and rheology (deformation rate, apparent viscosity, flow behavior index and consistency index) of a fermented dairy drink was studied. A completely randomized experimental design of two factors: percentage of whey (0, 5, 10 and 15% w/w) and type of milk (whole and skim) was used. The significance was determined using an analysis of variance (ANOVA). All properties analyzed except pH had statistically significant differences (P<0.05). The use of whole milk in comparison to skim milk generated an increase in soluble solids and viscosity of the beverage but caused a decrease in acidity and syneresis. The growth in whey concentration increased syneresis and apparent viscosity but decreased soluble solids and consistency index. The changes in properties are related to the contribution of fat from milk and the contribution of calcium and phosphate from whey, affecting both the interaction between the casein micelles and the water retention capacity, which changes the composition and fluidity of the beverage.